Validation of Two Kinetic Assays for the Quantification of Endotoxin in Human Serum - Christian Barro; Christian Barro; Anu Paul; Anu Paul; Fermisk Saleh; Fermisk Saleh; Tanuja Chitnis; Tanuja Chitnis; Tanuja Chitnis; Howard L. Weiner; Howard L. Weiner; Howard L. Weiner (Frontiers in Neurology, 2021)
Background: There is an emerging evidence of the role of the microbiome in neurological diseases. Endotoxin is a component of gram-negative bacteria and thought to be one of the possible signals between the gut microbiota and the immune system. Previous studies explored the blood levels of endotoxin using an endpoint chromogenic assay.Methods: We validated and compared the analytical performance of two kinetic assays for the quantification of endotoxin in serum: (1) the Limulus Amebocyte Lysate (LAL) Kinetic-QCL assay and (2) the turbidimetric LAL Pyrogent-5000 assay. We used the best-performing validated assay to measure the endotoxin level in 20 patients with multiple sclerosis (MS) and eight healthy controls.Results: The Pyrogent-5000 and QCL assay achieved similar performance in regard to spike recovery and linear dilution; however, the Pyrogent-5000 had a better signal to noise in the calibrator curve. By using the Pyrogent-5000 assay, we found that serum samples from MS patients and healthy controls have a similar level of endotoxin; hence, we did not find evidence to support a penetration of endotoxin in the blood of MS patients. Our findings do not exclude a role of endotoxin in mediating signals from the gut microbiota in MS patients directly at the gut–blood barrier where numerous antigen-presenting cells are actively sensing metabolites and bacterial products.